Analisis Olah Raga Menurut Prespektif Sunah Rosululloh Saw Dalam Implikasi Kesehatan Jasmani dan Rohani - Budi Wijaya; Dian Imam Saefullah (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2024)
Exercise is a physical skill in maintaining and improving the quality of health, both physical and spiritual health. Islam views health as very important because health is the main factor not only in realizing human relationships with their creator, but also contains comprehensive, harmonious, clear and logical values. In this discussion, we consider the Rosululloh saw's guidelines for sports and the importance of exercise for physical and spiritual health. The focus of this research concerns any sport from the perspective of the sunnah of Rosululloh saw as well as the implications for physical and spiritual health in relation to Rosululloh saw's guidelines. In this case, the researcher examines the hadith of the Prophet SAW through literature review by taking sources of the Prophet's hadith and their interpretations. Literature review is a research method with a qualitative approach by collecting data from the source to answer the focus of the research by drawing conclusions. Rosululloh SAW encouraged his friends, especially Muslims, to always do the recommended sports such as running, swimming, archery and horse riding. This aim is in addition to exercise. The military basis for agility and physical fitness also contains spiritual education values ​​such as responsibility, honesty, discipline, courage and so on. The benefits contained in sport, apart from physical health, are also spiritual health, which can build character for spiritual and emotional health. Sports law is permissible for those who carry it out as long as it does not contain gambling, immorality or harm to other people.